"He's a total TubeCrush": post-feminist sensibility as intimate publics. Issue 6 (2nd November 2018) - Evans, Adrienne; Riley, Sarah
Abstract: In this paper, we analyze the website TubeCrush, where people post and share unsolicited photographs of "guy candy" seen on the London Underground. We use TubeCrush as a case study to develop Berlant's intimate publics as a lens for examining post-feminist sensibility and masculinity in the liminal space between home/work. The paper responds to notions of reverse sexism and post-sexism used to make sense of women's apparent objectification of men in the digital space, by asking instead where the value of such images lies. We suggest that in TubeCrush, value is directed onto the bodies of particular men, creating a visual economy of post-feminist masculinity of whiteness, physical strength, and economic wealth. This celebration of masculine capital is achieved through humor and the knowing wink, but the outcome is a reaffirmation of urban hegemonic masculinity.